Evaluasi Keamanan Fitur Tarik Tunai Cardless pada Aplikasi BRImo Menggunakan PIECES - Kristoko Dwi Hartomo; Dearmelliani Tarigan (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2022)
Financial technology (fintech) is a technological development that makes it easier for us in the current digital era. One of the fintech applications in mobile banking services is the BRI Mobile (BRImo) application. BRImo application users still do not fully trust the security of the BRImo feature when withdrawing cash without an Automatic Teller Machine (ATM) card due to cybercrime, such as cases of online fraud. So in this study, we will analyze security and user satisfaction with the cardless cash withdrawal feature in the BRImo application. This study uses the PIECES framework method with six aspects: Performance, Information and Data, Control and Security, Efficiency, and Service. Data was collected by distributing questionnaires and processing data with the help of software version 3.0, namely Smart Partial Least Squares (Smart-PLS). The results from the study indicate that the quality of service and data information on the BRImo cardless cash withdrawal feature significantly influence Control and Security and BRImo user satisfaction.